A novel technique myomucosal rotational upper lip flap for anterior palatal fistula closure - Nicolas Solano; Francisco Carcelén; Rafael Oropeza; Patricia López (Wolters Kluwer Medknow Publications, 2024)
Palatal fistulas are a pathological condition where there is a connection between the nasal area and the oral cavity, being one of the most frequent complications in cleft palate surgery. Palatal fistulas can cause esthetic defects and functional alterations in both feeding and speech of patients. Anterior palatal fistulas are the least common but represent a great surgical challenge for the surgeon because of their location and poor amount of tissue for closure. The purpose of this article is to present a novel technique of performing an upper lip myomucosal rotation flap for the closure of an anterior fistula, taking advantage of the labial tissue for a tension-free suture in the area of the fistula. Our technique allowed an adequate management of the fistula with low morbidity and without flap necrosis, proposing it as a useful technique for the closure of anterior fistulas.